Silicato de alumínio em substrato para produção de mudas de Corymbia citriodora - Castro, Edicarlos Batista [UNESP]; Santos, Leonardo David Tuffi; Fernandes, Luiz Arnaldo; Tajima, Claudio Yukio (FapUNIFESP (SciELO), 2016)
The aim was to verify the aluminum silicate efficiency on substrate composition for Corymbia citriodora seedlings production. The design was a completely randomized design with five treatments and eight replicates. The composition of the substrate consisted of charcoal powder, bovine manure, eucalyptus husk and commercial substrate. It was added on 0 (evidence), 5, 10, 15 and 20% aluminum silicate in the treatments. The seedling quality index, height, the collar diameter, root fresh and dry mass, mean and full foliar area and ratio between root and aerial part dry mass and were not influenced. For aerial fresh and dry mass the evidence were higher than 2.59 and 4.93 respectively. Nevertheless, the addiction until 12.2% showed increasing gains on leaves number. The aluminum silicate to produce C. citriodoraseedlings emergesas a potential target of this alternative residue.
Use of aluminum silicate partial substitution in the substrate for seedlings production Corymbia citriodora
Keywords: Forest species; Industrial residual; Seedling quality; Silicate